Final answer:
The expression 10 + 2p - 3r, with p=3 and r=-2, is evaluated by substituting the given values which results in an answer of 22.
Step-by-step explanation:
The student has been asked to evaluate the expression 10 + 2p - 3r, given the values of p = 3 and r = -2. We will substitute these values into the expression as follows:
10 + 2(3) - 3(-2)
First, multiply 2 by 3 (for 2p) and -3 by -2 (for -3r):
10 + 6 + 6
Now, we add all terms together:
10 + 6 + 6 = 22
The evaluated expression equals 22.